2016
DOI: 10.5194/acp-16-907-2016
|View full text |Cite
|
Sign up to set email alerts
|

A review of approaches to estimate wildfire plume injection height within large-scale atmospheric chemical transport models

Abstract: Abstract. Landscape fires produce smoke containing a very wide variety of chemical species, both gases and aerosols. For larger, more intense fires that produce the greatest amounts of emissions per unit time, the smoke tends initially to be transported vertically or semi-vertically close by the source region, driven by the intense heat and convective energy released by the burning vegetation. The column of hot smoke rapidly entrains cooler ambient air, forming a rising plume within which the fire emissions ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
146
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(148 citation statements)
references
References 97 publications
(184 reference statements)
1
146
0
1
Order By: Relevance
“…We have added 2013 forest fire emissions which were originally created for the 2013 FireWork forecasts to the anthropogenic point-source emissions used in the base case simulation, and have modified the GEM-MACH model to be able to accommodate the changing number of major point sources each day (as the number of fires changes daily). Fire plume rise is an ongoing area of investigation (e.g., Heilman et al, 2014;Paugam et al, 2016); smoldering emissions tend to be emitted directly at the surface, whereas flaming emissions can inject plumes to the upper troposphere. Here, we have set all fire emissions to be distributed evenly throughout the boundary layer, which is a simplification but one that averages out smouldering and flaming plume heights.…”
Section: Addition Of Forest Fire Emissionsmentioning
confidence: 99%
“…We have added 2013 forest fire emissions which were originally created for the 2013 FireWork forecasts to the anthropogenic point-source emissions used in the base case simulation, and have modified the GEM-MACH model to be able to accommodate the changing number of major point sources each day (as the number of fires changes daily). Fire plume rise is an ongoing area of investigation (e.g., Heilman et al, 2014;Paugam et al, 2016); smoldering emissions tend to be emitted directly at the surface, whereas flaming emissions can inject plumes to the upper troposphere. Here, we have set all fire emissions to be distributed evenly throughout the boundary layer, which is a simplification but one that averages out smouldering and flaming plume heights.…”
Section: Addition Of Forest Fire Emissionsmentioning
confidence: 99%
“…When a fire is in the flaming combustion stage, the intense heat from the burning vegetation creates a rising plume which interacts with the ambient atmosphere and transports the fire emissions vertically (Freitas et al, 2006;Paugam et al, 2016). Because of this fire-induced convection, biomass burning is one of the few processes that emits large quantities of aerosols and trace gases well above the planetary boundary layer (PBL), sometimes even reaching the upper troposphere/lower stratosphere (Andreae et al, 2004;Fromm et al, 2005;Dahlkötter et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The algorithms available today are summed up in Paugam et al (2016) and Veira et al (2015a). They can be divided into two families: semiempirical models (Achtemeier et al, 2011, andSofiev et al, 2012, for example) and numerical one-dimensional plume rise models (PRMs) such as the one developed by Latham (1994) and further refined by Freitas et al (2007) and others.…”
Section: Introductionmentioning
confidence: 99%
“…Val Martin et al (2010) indicated that both the fire intensity and the stability of the atmosphere are crucial for the effective source height. A recent review of the representation of plume injection heights in atmospheric models was performed by Paugam et al (2016).…”
Section: Introductionmentioning
confidence: 99%